Nanobodies: A Review of Generation, Diagnostics and Therapeutics - Jin, Bo-kyung; Odongo, Steven; Radwanska, Magdalena; Magez, Stefan (International Journal of Molecular Sciences, 2023)
Nanobodies, also referred to as single domain-based VHHs, are antibody fragments derived from heavy-chain only IgG antibodies found in the Camelidae family. Due to their small size, simple structure, high antigen binding affinity, and remarkable stability in extreme conditions, nanobodies possess the potential to overcome several of the limitations of conventional monoclonal antibodies. For many years, nanobodies have been of great interest in a wide variety of research fields, particularly in the diagnosis and treatment of diseases. This culminated in the approval of the world’s first nanobody based drug (Caplacizumab) in 2018 with others following soon thereafter. This review will provide an overview, with examples, of (i) the structure and advantages of nanobodies compared to conventional monoclonal antibodies, (ii) methods used to generate and produce antigen-specific nanobodies, (iii) applications for diagnostics, and (iv) ongoing clinical trials for nanobody therapeutics as well as promising candidates for clinical development.
Keywords: Therapeutics; Diagnostics; Nanobody; Nanobody generation; Nanobody production